Training and Marketing Channel as Determinant of Empowerment of Rural Self Help Group Women Members - Kumari, Neelam; Malik, Joginder Singh; Ghalawat, Suman (Indian Journal of Extension Education, 2021)
The present study was conducted on 120 randomly selected respondents from Bhiwani and Bawani Khera blocks of Bhiwani district of Haryana state. The study revealed that the majority of the respondents belonged to the young age group, were illiterate, and belonged to nuclear families of medium family size. Hundred per cent of the respondents were active with social participation in one organization. The training received score was obtained highest for income generation (weighted mean score 2.00 and rank I), followed by loaning and dairy, and agriculture ranked II and III, respectively. Similarly, for marketing channels, individual sale mode of marketing ranked first, followed by ˜group contacts with shopkeepers in village/nearby village, ˜group contacts withÂ shopkeepers in cities and ˜group sale respectively. Association between independent variables with training and marketing channels was found to be positively correlated. It was interesting that a negligible percentage ofÂ respondents performed tasks of income-generating activities and marketing, which were not fruitful for them.